Logistics Management Contributions of the Section Logistics of the German Academic Association for Business Research, 2015, Braunschweig, Germany - Mattfeld, Dirk.; Spengler, Thomas; Brinkmann, Jan.; Grunewald, Martin; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This contributed volume contains the selected and thoroughly reviewed research papers presented at the conference on logistics management LM2015 in Braunschweig, Germany. The conference of the special interest group in logistics of the German Academic Association for Business Research (VHB) was held in conjunction with the special interest group on production of the VHB. Thus, the papers reflect the current state-of-the-art in logistics and supply chain management while focusing especially on aspects of production logistics, i.e., facility layout, inventory management, line configuration, or flexible production.
Condition-Based Maintenance Planning within the Aviation Industry -- Considering Small and Medium-Sized Suppliers in Public Procurement - The Case of the German Defence Sector -- Integration of Cultural Aspects in Supplier Evaluation -- RoRA-SCM - Review of the Integration of Flexibility Planning in Supply Chains -- Coordination in Multimodal Supply Chains: Drafting an Agent-based Exchange -- Flexibility of 3PL Contracts: Practical Evidence and Propositions on the Design of Contract Flexibility in 3PL Relationships -- Extended Model Formulation of the Facility Layout Problem with Aisle Structure -- Integrated Facility Location, Capacity, and Production Planning in a Multi-Commodity Closed Supply Chain Network -- Integrated Make-Or-Buy and Facility Layout Problem with Multiple Products -- Qualification and Competence Related Misfits in Logistics Companies: Identification and Measurement -- A Lot Streaming Model for a Re-Entrant Flow Shop Scheduling Problem with Missing Operations -- Identifying Complexity-Inducing Variety: Adapting ClustalW for Semi-conductor Industry -- Consideration of Redundancies in the Configuration of Automated Flow Lines -- Prepositioning of Relief Items Under Uncertainty: A Classification of Modeling and Solution Approaches for Disaster Management -- Forecasting Misused E-Commerce Consumer Returns -- A Rollout Algorithm for Vehicle Routing with Stochastic Customer Re-quests -- A Real-World Cost Function Based on Tariffs for Vehicle Routing in the Food Retailing Industry -- An Adaptive Large Neighborhood Search for the Reverse Open Vehicle Routing Problem with Time Windows -- A Two-Stage Iterative Solution Approach for Solving a Container Transportation Problem -- Vehicle Routing and Break Scheduling by a Distributed Decision Making Approach.
Keywords: Industrial Management; Production management; Transportation engineering; Traffic engineering; Industrial Management; Operations Management; Transportation Technology and Traffic Engineering